Fosforläckage från växtodling - Huselius, Lotta (2009)
Phosphorus is essential to all plants and is taken up from the soil as the ion H2PO4 - (and to some extent HPO42-). Plant availability depends on, among other factors, the soil pH. In order to provide for plant available phosphorus, it is applied as mineral fertilizers and farmyard manure. However, that causes phosphorus leaching from arable land to surrounding surface waters and lakes and contributes to the eutrofication. There are three types of soils in Sweden that are at higher risk of contributing to phosphorus leakage. There are clay soils with an extended macropore flow, silty soils that are prone to erosion and sandy soils with a low sorption capacity. Different measures are taken to limit the phosphorus leaking from soils. The amount of phosphorus fertilization allowed is restricted by The Swedish Board of Agriculture, with recommendations not to apply P above a soil P status III according to the P-AL scale. Phosphorus losses through the soil may be limited by different cultivation practices. Fertilizers should not be applied on wet or frozen land since that leads to large losses through surface runoff. Using catch crops and buffer zones around the field are useful in some cases, but can during some circumstances, for instance repeated freezing and thawing. It has been shown that the soil type is more crucial than cultivating measures in determining phosphorus losses. Several of the measures are effective on a short-term basis, but need to be developed to be effective on longer terms.